Factors that influence cadre participation in the managing the family planning program in Banjarmasin City - Mirawati; Mariati , Nelly; Aulia , Fika; Rahmah , Afiatun (Journal of Health Technology Assessment in Midwifery, 2024)
The increasing population can lead to complex problems. One way to reduce the population is by implementing family planning programs. The success of the family planning program is largely determined by the participation of family planning cadres in each region. The purpose of this research was to analyze the factors that influence cadre participation in the management of family planning programs. The research method uses a cross-sectional design by analyzing the influence of age, education, length of time as a cadre, appreciation and motivation on participation. The research was conducted in the city of Banjarmasin. The sampling technique used is purposive sampling with a sample size of 61 cadres. Data analysis using the Kruskal Wallis test. The results of the study found that there was an influence of motivation on cadre participation with a p value of 0.005 < α (0.05), while the variables of age, education, length of time to cadre and appreciation did not have a significant effect. The motivation of cadres must always be improved for the success of family planning programs.